Wearable Technology Athleisure Fashion dengan LED dan Mikrokontroler Untuk Mendukung Keamanan Pengguna - Olivia Gondoputranto; Stephanus Evert Indrawan (JURNAL RUPA, 2022)
With the Rise of Athleisure Fashion Globally, from the beginning of Pandemic Covid 19 until nowadays, has impacted the current society’s lifestyle. People tend to prefer a functional and easy-to-coordinate style, so the Athleisure concept fits mostly for the busy urban society. Along with Athleisure, there is also another emerging trend that is growing rapidly. It’s a Trend for wearable tech fashion products. Indonesia predicted to be one of the great potential market for wearable technology because the people are very adaptive to technology although they haven’t familiarized with wearable technology in the form of fashion. This research takes the gap to introduce and give awareness about wearable technology in the form of fashion by creating an Athleisure Fashion with Wearable Technology implementation. To enhance its user’s safety factor by designing athleisure clothes that emitting lights using LED Strip and LED Array as signals that can be controlled by microcontroller. Using Fashion Design Method for Wearable Technology to integrate fashion design creative process, and scientific method to create the wearable tech in the form of athleisure fashion. Then conduct interviews with expert and user to gain feedbacks. The result showed that the LED signals emitted from the clothes are easy to understand for most people, and possess aesthetic value for the users. Keywordsarduino, athleisure, fashion, LED, microcontroller, technology, wearable technology